Dipeptidyl peptidase 1 inhibitors for inflammatory respiratory diseases: mechanisms, clinical trials, and therapeutic prospects - Zhang, Dandan; Zhang, Wenwen; Hu, Ping; Zhang, Wei (Frontiers in Pharmacology, 2025)
Dipeptidyl peptidase 1 (DPP1) inhibitors constitute a major advance in respiratory disease therapeutics. Through selective blockade of neutrophil serine protease (NSP) activation, these agents establish novel treatment paradigms for inflammatory respiratory conditions characterized by neutrophil-driven pathology. This comprehensive review examines the development status, clinical efficacy, and safety profile of DPP1 inhibitors in neutrophil-driven diseases, particularly non-cystic fibrosis bronchiectasis (NCFBE) and chronic obstructive pulmonary disease (COPD). Leading compounds including brensocatib, BI 1291583, and HSK31858 have demonstrated substantial clinical efficacy. In the pivotal WILLOW Phase II trial, brensocatib significantly extended time to first exacerbation (hazard ratio 0.58–0.62, p < 0.05) in bronchiectasis patients. The subsequent ASPEN Phase III trial confirmed these findings, with brensocatib reducing annualized exacerbation rates by 21% (10 mg) and 19% (25 mg) compared to placebo (adjusted p = 0.004 and p = 0.005, respectively). Similarly, HSK31858 demonstrated comparable efficacy in Chinese patients, reducing exacerbation risk by 48%–59% in the SAVE-BE trial. While the clinical phenotype observed in Papillon-Lefèvre syndrome (PLS) necessitates careful monitoring of skin and periodontal health during DPP1 inhibition therapy, clinical trials have shown these adverse events occur at low frequencies (1%–4%) and are predominantly mild to moderate in severity. Future research priorities include establishing standardized monitoring protocols for dermatological and periodontal health, developing biomarkers for patient stratification, validating long-term safety profiles, and optimizing combination treatment strategies. With brensocatib potentially becoming the first approved mechanism-specific therapy for bronchiectasis by mid-2025, DPP1 inhibitors represent a paradigm shift in managing neutrophil-mediated respiratory diseases.